Sodelovanje stanovalcev kot pogoj za uspešno izvedbo prenove stanovanjskih sosesk - Sendi, Richard (Urbani izziv, 2005)
The article presents findings from the research project titled Rehabilitation of housing estates in Ljubljana. The research was conducted in the western part of the Savsko naselje neighbourhood in Ljubljana. The introduction bringsa brief description of the theoretical framework of the research. In continuation results of field work are presented, whereby special emphasis is given to the views of residents to rehabilitation and improvements to their living environment. Confrontation of attitudes to issues pertaining to the housing estate with real actions (or non-actions) by local authority show thatpresently there are large, potentially damaging contradictions between thetwo actors. We can ascertain that at present the municipal departments are accountable for the present conflicts, especially those responsible for housing provision and living quality. We are adamant that present planning andmanagement of housing estates - top-down - is inadequate and inefficient. As soon as possible it should be substituted with contemporary approaches thathave been pursued for some time in more developed countries. The hypothesis of the article is that rehabilitation of housing estates is not possible without active resident participation.
Keywords: bivalno okolje; kvaliteta; Ljubljana; prenova; stanovanja; stanovanjska naselja; urbana sociologija